Impaired Upper Airway Muscle Function with Excessive or Deficient Dietary Intake of Selenium in Rats - David P. Burns; Sarah E. Drummond; Stefanie Wölfel; Kevin H. Murphy; Joanna Szpunar; Ken D. O'Halloran; John J. Mackrill (MDPI AG, 2024)
Obstructive sleep apnoea (OSA) involves impaired upper airway muscle function and is linked to several pathologies including systemic hypertension, daytime somnolence and cognitive decline. Selenium is an essential micronutrient that exerts many of its effects through selenoproteins. Evidence indicates that either deficient or excessive dietary selenium intake can result in impaired muscle function, termed nutritional myopathy. To investigate the effects of selenium on an upper airway muscle, the sternohyoid, rats were fed on diets containing deficient, normal (0.5 ppm sodium selenite) or excessive (5 ppm selenite) selenium for a period of two weeks. Sternohyoid contractile function was assessed ex vivo. Serum selenium levels and activity of the glutathione antioxidant system were determined by biochemical assays. The abundance of three key muscle selenoproteins (selenoproteins -N, -S and -W (SELENON, SELENOS and SELENOW)) in sternohyoid muscle were quantified by immunoblotting. Levels of these selenoproteins were also compared between rats exposed to chronic intermittent hypoxia, a model of OSA, and sham treated animals. Although having no detectable effect on selected organ masses and whole-body weight, either selenium-deficient or -excessive diets severely impaired sternohyoid contractile function. These changes did not involve altered fibre size distribution. These dietary interventions resulted in corresponding changes in serum selenium concentrations but did not alter the activity of glutathione-dependent antioxidant systems in sternohyoid muscle. Excess dietary selenium increased the abundance of SELENOW protein in sternohyoid muscles but had no effect on SELENON or SELENOS. In contrast, chronic intermittent hypoxia increased SELENON, decreased SELENOW and had no significant effect on SELENOS in sternohyoid muscle. These findings indicate that two-week exposure to selenium-deficient or -excessive diets drastically impaired upper airway muscle function. In the sternohyoid, SELENON, SELENOS and SELENOW proteins show distinct alterations in level following exposure to different dietary selenium intakes, or to chronic intermittent hypoxia. Understanding how alterations in Se and selenoproteins impact sternohyoid muscle function has the potential to be translated into new therapies for prevention or treatment of OSA.